VARIASI PEMAKAIAN TINGKAT TUTUR BAHASA JAWA DI WILAYAH EKS KARESIDENAN KEDU (KAJIAN SOSIODIALEKTOLOGI) - Astuti, Eka Yuli (Lingua, 2010)
This research aims at studying the use of Javanese in Ex. Karesidenan Kedu (abbreviated as BJKK). Itis based on sociodialectology approach. This study deals with the social variables of the subjects includingtheir education, occupation, and age; besides rural-urban distinction that influences the variations BJKKspeakers. The language uses are classified into variations related to phonological, morphological,syntactical, lexical, speech-level aspects.The drawing of primary data was based on a research instrument containing 1001 questionsqualitatively developed from Swadesh List containing 200 new base-word items. The research location (RL)was classified into three RLs according their historical relations. There are RLs, i.e. RL -1 Magelang, RL -2Kebumen, RL -3 Dieng Wonosobo. The criterion of RL selection was based on the BJJS similarities (OP-1),Banyumas as well as Sundanese (RL-2) dialect influence, and lingual characteristics that are similar to thatof Banyumas dialect and BJJS (RL-3). All data have been analyzed using descriptive method.The research finding on phonological level showed that among he speakers at BJKK the phonologicalsystem has 8 vowels and 20 consonants. The BJKK words were formed through morphological process,such as affixation, reduplication, and composition process. In syntactical level, this research founddeclarative, interrogative, and imperative sentences based on the function and the related context, whosevariation can be applied in various speech level context such as Ng, Md, Kr, and KI. The acquisition ofspeech level of the three OP and six variables are different from each other. The speakers in RL-1 acquirethe speech level better than the ones in RL -2 and RL -3. The educated speakers whose occupation werefarmers, acquired the speech level better than the other variables.Among the speakers of Javanese at BJKK, there was a variety uses of phones and morphs such asthe use of {-aken} affix. This affix was intensively used at RL-2 and RL-3 as imperative Ng marking affix. Thistype of suffix was not used at BJJS whose affix was used in Kr level. The syntactical variation took place inthe part of imperatives and the use of dialect such as [si], [sih], [je], [lah], [.diG] used in informal situation.The dominating variety of lexicon that is different from BJJS was found in RL-2. In the speech level, thedominating variety was found in Kr level. BI interferences were intensively used in peripheral location. That isnot an extraordinary phenomenon when the speakers have obstacles to choose the best speech level order.Key words: sociodialectology, social variation, speech level variation